Coral Fish Community of Chaetodontidae in the Coral Reef of Poopoh Village, Tombariri District, Minahasa Regency - Unstain N. W. J. Rembet; Ari B. Rondonuwu; Laurentius T. X. Lalamentik (Jurnal Ilmiah PLATAX, 2018)
This study was aimed to determine the number of species, number of individual, density, and the structure of community of Chaetodontidae. This research was conducted in the waters of Poopoh Village, Tombariri District, Minahasa Regency, North Sulawesi Province. Data collection was carried out at a depth of 5 meters with the Underwater Visual Census (UVC) method with an observation area of 250 m2.  Chaetodontidae have been found on the coral reefs of Poopoh Village, Tombariri District, consisting of 3 (three) genera,  Chaetodon, Forcipiger, and Heniochus with 13 species and 51 number of individuals. The diversity of species in Poopoh is categorized as moderate. The highest density of coralivorous fish found in Chaetodon kleinii species is 360 individuals / Ha followed by Heniochus acuminatus which is 240 individuals / Ha. The diversity of Chaetodontidae in this location is high. This condition is also seen in the maximum index (Hmax) which is not far above the value of H '.Keywords: Coral reef, Chaetodontidae, Poopoh Village ABSTRAKTujuan penelitian ini yaitu untuk mengetahui jumlah spesies, kelimpahan individu, densitas,  dan struktur komunitas ikan Chaetodontidae.  Penelitian ini dilakukan  di perairan Desa Poopoh, Kecamatan Tombariri, Kabupaten Minahasa, Provinsi Sulawesi Utara.  Pengambilan data dilakukan pada kedalaman 5 meter dengan metode Underwater Visual Census (UVC) dengan luas areal pengamatan adalah 250 m2.   Ikan karang Chaetodontidae  telah ditemukan di terumbu karang Desa Poopoh, Kecamatan Tombariri,  terdiri dari 3 (tiga) marga yaitu Chaetodon, Forcipiger, dan Heniochus dengan 13 spesies dan 51 individu. Keragaman spesies di Poopoh dikategorikan sedang. Densitas tertinggi ikan koralivora ditemukan pada jenis Chaetodon kleinii yaitu 360 individu/Ha diikuti Heniochus acuminatus yaitu 240 individu / Ha. Keanekaragaman spesies Chaetodontidae di lokasi ini tergolong tinggi. Kondisi ini terlihat juga pada indeks maksimum (Hmax) yang tidak berada jauh di atas nilai H ’.Kata Kunci: Terumbu karang, Chaetodontidae, Desa Poopoh, .